Description Study Of Millon's Personality Types On Marital Adjustments For Young Couples In Bandung - Heryana, Nur Rakhmanto; Anissaniwaty, Myrna; Hakim, Alfi Fauzia (Insight: Jurnal Ilmiah Psikologi, 2022)
ne of the problems in marriage is due to by poor interaction between partners. The personality type of each influences this interaction. This study aims to determine the effect of Millon's personality type on marital adjustment. The subjects of this Research areÂ Â  five married couples with a marriage age of 1-5 years. The technique used in this study is a non-probability sampling technique, namely purposive sampling. Method to measure marital adjustment, this study used the Dyadic Adjustment Scale (DAS), while to measure individual personality types, this study used the Millon Clinical Multiaxial Inventory-IV (MCMI-IV). MCMI-IV is a measuring tool that can represent a person's personality type. MCMI-IV Invalid Guidelines 1. V Scale > 1, 2. W Scale > 19, X Scale < 7 and > 114, 1-8B Scale (All) < 60 (BR). to test the research hypothesis using MCMI-IV and DAS software. The result is that there is an influence of personality type with marital adjustment. Conclusion Certain personality types correlate with patterns of marital adjustment between partners.